2021
DOI: 10.3389/fsufs.2021.684808
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Evapotranspiration and Water Requirements of Strawberry Plants in Greenhouses Using Environmental Data

Abstract: Farmers routinely determine irrigation requirements from visual observations and cultivation experience, but this can lead to under- or over-irrigation. To establish precise irrigation technology for strawberry cultivation, the average daily evapotranspiration and water requirements were estimated according to the environmental data: air temperature and humidity from the center of the greenhouses and solar radiation from outside greenhouses. Makkink FAO24 equations (temperature and cloudiness) were used to est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Third, daily air temperature and relative humidity reflect other key environmental factors due to their high correlations. Ahn et al (2021) and Jo et al (2021) showed that the trend in air temperature was similar to that of soil temperature and photosynthetic active radiation, and the trend in relative humidity was related to vapor pressure deficit. Lastly, in our previous study, the correlation coefficients between daily air temperature and relative humidity and strawberry fruit yield were 0.82 and −0.93, respectively ( Sim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…Third, daily air temperature and relative humidity reflect other key environmental factors due to their high correlations. Ahn et al (2021) and Jo et al (2021) showed that the trend in air temperature was similar to that of soil temperature and photosynthetic active radiation, and the trend in relative humidity was related to vapor pressure deficit. Lastly, in our previous study, the correlation coefficients between daily air temperature and relative humidity and strawberry fruit yield were 0.82 and −0.93, respectively ( Sim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 88%
“…[3] Daily average air temperature and relative humidity can substitute other environmental factors. Ahn et al (11) and Jo et al (19) displayed that the trend in air temperature was similar to that of soil temperature and photosynthetic active radiation, and the trend in relative humidity was related to vapor pressure de cit. [4] In our previous study, the correlation coe cients between daily average air temperature and relative humidity, and strawberry fruit yield, were 0.82 and − 0.93, respectively (12).…”
Section: Discussionmentioning
confidence: 99%
“…The prospects for this technology is high promising, given its demonstrated ability to double farmers' earnings outside the rainy season. The success in chili cultivation, yielding 6.75 t/ha and generating substantial income, serves as a compelling model for other crops and regions facing similar challenges (Alam et al, 2010;Burney et al, 2010;Jo et al, 2021;Portugal et al, 2020). The economic viability of the system, which indicated by its positive NPV, high IRR, favorable PI, and short PP, makes it an attractive option for farmers and investors alike.…”
Section: Substainbility and Prospectmentioning
confidence: 99%